Validation of a Novel High‐Sensitivity Cardiac Troponin‐T Assay in Horses. (June 2014) - Shields, E; Passante, S; Massie, S; Seiden‐Long, I; Leguillette, R
Abstract : Introduction: Cardiac troponin‐I (cTn‐I) has been previously validated in horses. Newer high sensitivity troponin assays have recently become available that are now the standard in human cardiology. The objective was to validate the high‐sensitivity cardiac troponin‐T (hscTn‐T) assay for use in horses and to determine the biological variation within and between horse breeds. Methods: Samples were analysed using the hscTn‐T assay reagent (Roche, Cobas c501). Method validation included linearity, lower limit of quantitation (LLQ), freeze‐thaw stability, within‐and between‐run precision, and comparison with cTn‐I (Abbott iSTAT, Deming regression). Normal range and biological variation included healthy horses (n = 120; age = 7.2 ± 0.5 years (SE)) representing 5 breeds. Results: Assay was linear from 3–391 ng/L. The LLQ was validated at 3 ng/L. Stability of samples was unaffected by 3 freeze‐thaw cycles. Within‐run mean (±SD) was L1 = 6.50 (±0.97), L2 = 10.1 (±0.88), L3 = 15.3 (±0.82) ng/L and between‐run mean (±SD) was L1 = 12.2 (±1.03), L2 = 57.0 (±4.82), L3 = 256 (±23.1) ng/L. Comparison with cTn‐I assay showed excellent correlation (range: 8–3535 ng/L, r = 0.9998). Bias was evident in the regression results [hscTnT = (0.6153 ± 0.002809)*(cTnI*1000) − (11.53 ± 5.462)]. The 95 th and 99 th percentile of the normal distribution in healthy horses was 4 and 6 ng/L. Between breed, diurnal effect and between day variation was not detectable due to low concentrations of hscTnT. Conclusions: This study established reference intervals for hscTn‐T assay in healthy horses and the performance characteristics of hsTn‐T assay in horse samples. Normal population distribution was mostly below the detection limit of the assay. The hscTn‐T assay will likely establish the standard in early detection of cardiac pathologies in horses. Ethical Animal Research: This study was approved by the Veterinary Sciences Animal Care Committee (protocol number AC12‐0049).Sources of funding: UCVM internship fund.Competing interests: none.